2005
DOI: 10.1017/s0022215105006663
|View full text |Cite
|
Sign up to set email alerts
|

Driving and otolaryngology: do we know the rules?

Abstract: Certain medical conditions may affect one's ability to drive safely. In the United Kingdom, the Driver and Vehicle Licensing Agency (DVLA) issues guidelines outlining which medical conditions drivers must notify them of. In order to assess our knowledge of, and ability to apply, the current DVLA guidelines with regard to otolaryngological conditions, a postal survey was sent to all otolaryngologists in Scotland. The responses obtained suggest that the current DVLA guidelines are not well understood or easily a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 4 publications
0
8
0
1
Order By: Relevance
“…While a significant number of patients in our study indicated that they would have liked more clarity on this, and while the Dutch government assumes that health professionals are under an obligation to inform patients about potential limitations related to driving, in 92% of the patients with dizziness and vertigo in our study, the topic of driving was not discussed. This could be because doctors are not aware of the requirements imposed by national law ( 8 , 9 ). Another explanation could be that doctors in the Netherlands regard the current legislation as too strict.…”
Section: Discussionmentioning
confidence: 99%
“…While a significant number of patients in our study indicated that they would have liked more clarity on this, and while the Dutch government assumes that health professionals are under an obligation to inform patients about potential limitations related to driving, in 92% of the patients with dizziness and vertigo in our study, the topic of driving was not discussed. This could be because doctors are not aware of the requirements imposed by national law ( 8 , 9 ). Another explanation could be that doctors in the Netherlands regard the current legislation as too strict.…”
Section: Discussionmentioning
confidence: 99%
“…This means people are often unable to work, [12][13][14][15] and it has a significant impact on their lifestyle. [16][17][18][19] It is surprising that there is a reported lack of knowledge at patient and practitioner level. 17,18 Consequently, driving was not considered in 92 per cent of patients attending a centre for dizziness and balance disorders.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19] It is surprising that there is a reported lack of knowledge at patient and practitioner level. 17,18 Consequently, driving was not considered in 92 per cent of patients attending a centre for dizziness and balance disorders. 19 However, given its importance, the topic of driving and dizziness or vertigo should always be addressed in those presenting with these symptoms, 20 and in patients taking medication that causes dizziness or drowsiness, 20 as data are consistent regarding the effects of medications used for dizziness and vertigo on driving ability.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 There is a lack of uniformity regarding driving regulations of the dizzy patient and a lack of consensus for clinicians on how to evaluate driving ability in dizzy patients. 4,6 This can be attributed to discordant literature. For instance, a recent communication of DIZZYNET (a European network initiative for vertigo and balance research) with data gathered by an insurance company shows there is no increased risk of traffic accidents in people with acute unilateral vestibulopathy or MD.…”
Section: Introductionmentioning
confidence: 99%